Systematic Studies of Philippine cheyletid mites(Acarina, Cheyletidae) IV. The genus cheyletus Latreille - Corpuz-Raroz, L.A. (1988)
Philippine species and collections of Cheyletus are reviewed with emphasis on those associated with birds or their nests. A new species, C. philippinensis, is described from body feathers of an undetermined woodpecker, and C. malayensis Cunliffe is added as a new record. A key to the more commonly cited world species of the genus is included.
Includes bibliographical references (page 334)
Keywords: Zoology; Philippine cheyletid mites (Acarina, Cheyletidae); Birds